Incidencia de colágeno de pollo y temperatura del proceso en la calidad proteica de salchicha escalcada. - Basurto Calderón, Carlos Andrés (2015)
The objective of this research was to evaluate the protein quality of chicken sausage using collagen from chicken legs in different percentages. The formulation for this sausage was calculated by the number Feder. An experimental design was completely randomized in factorial arrangement a x b where a represents the percentage of collagen (2%, 4% and 8%) and b corresponds to the scalding temperature (70 ° C and 75 ° C). A experimental unit of 3 kg of sausage was used. All treatments, as variables to measure the sensory acceptance of all treatments was established microbiological analyzes. The product was performed as scalded fine paste sausage. The results of sensory analysis were entered into spss version , where the treatments 1 with 2% collagen and treatment 2 with 4% collagen at 70 ° C were better as unskilled judges, these 2 treatments were under nutrition analyzes such as: protein, fat and moisture, where it was verified that the sausages of treatment 1 has a high percentage of protein, moisture, and a low percentage of fat while treatment 2, scored lower percentage of protein , humidity and higher percentage of fat, regarding treatment production costs in both treatments are similar and are type I sausages and besides having good organoleptic characteristics, as conclusion the chicken collagen influences the protein quality sausage.